Development of a Human Accompanying Wheelchair using Ultrasonic Tethering - Pingali, Theja Ram (Université d'Ottawa / University of Ottawa, 2019)
In social situations, people who use a powered wheelchair must divide their attention between navigating the chair and conversing with people. As a solution that maintains a good conversation distance between the wheelchair and the accompanying person, a wheelchair control system was introduced to provide automated side-by-side following by wirelessly tethering the wheelchair to the person. This thesis designed, developed, and evaluated a wireless tethering system using ultrasonic sensors. Two ping sensors and three piezoelectric ultrasonic transducers were used to identify the accompanying person and determine their pose. A trajectory algorithm determined the person’s direction of motion and a drive control algorithm determined the wheelchair’s required direction by maintaining a comfortable conversation distance between the person and the wheelchair user. A plug-and-play prototype was developed using commercially available components and the firmware was implemented using an open-source platform. The prototype developed in this thesis was mounted to a Permobil F3 Corpus powered wheelchair with a modified Eightfold Technologies SmartChair Remote, which controlled the wheelchair direction. Results demonstrated that the system can navigate a wheelchair beside an accompanying person and maintain a comfortable conversation distance, which is advantageous for users who require hands-free wheelchair control during social activities.
Keywords: Smart wheelchairs; Ultrasonic sensors; Social following; Ultrasonic tethering; Side-by-side following; Tethering